The possibilities and framework of conditions of organisational development at a particular administrative body - Elekes, Edit (Acta Agraria Debreceniensis, 2014)
The demand for the recognition, identification and introduction of measures aimed at improving organizational culture and the efficiency of management and leadership plays a crucial role in the life of every organization, including the law enforcement bodies as well. The tasks and responsibilities of the Hungarian Police Force have changed considerably both in terms of quantity and quality since Hungary’s accession into the European Union first, and since the country’s joining the Schengen Zone. We are now facing problems formerly unheard of (e. g. the integration of the police force and the border guard, joining the Schengen Zone, the emergence of new forms of crime). As border control within the Union stopped, organized crime has become more powerful. The changes are by no means over: in order to improve the subjective sense of security of the population and to advance organizational efficiency, a number of changes are being implemented at present. For the internal security of the member states of the Union and for the improvement of the efficiency of police work in the member states, the use of consciously coordinated management methods is indispensable. These efforts are the subject of this essay. A police force is an partially open system, the work of which is influenced by a number of external processes and factors. The organizational culture of a police force is determined by its traditions on the one hand, and by the demands to develop its functions as an authority and a service provider on the other. It is undeniable that any conscious effort in shaping and developing the organizational culture of the police requires special competences and commitment from the leaders of the organization. Furthermore, it is also necessary to modernize the management tasks. It applies to all the levels of leadership, from the head of a patrol to the supreme commander of the police force. The organizational scheme of the police force is that of a functional, linear system. Such an organization is characterized by a relatively high degree of inflexibility, a slow and cumbersome reaction to external changes. All these may adversely influence organizational efficiency. It therefore appears to be necessary to examine the present structure of police, and survey the possibilities of modernization. Modernization does not necessarily mean a change in the structure; it may be restricted to changes in organizational culture, the creation of an atmosphere favourable for reforms, and the coordination of diversified structures. In this paper I wish to demonstrate some of the possibilities of improving organizational culture and organization development, based upon the findings of a specific survey.